Holistic healing : Old Testament insights on sickness and healing - for churches in Africa confronted by HIV / Aids : : general - Zyl, Danie C. Van (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2008)
Notions on sickness and healing in the Old Testament are explored with reference to the HIV / Aids pandemic. Over and above simply collecting insights from the Old Testament, a more 'involved reading' of texts, particularly of Psalms, as suggested by Brueggemann, is argued and illustrated from Psalm 38. Perspectives from the Umwelt and the socio-religious reality in Ancient Israel are presented in order to create a framework for understanding Old Testament perspectives on sickness and healing. Furthermore, perspectives on sickness and healing from African world views and the practices in African faith healing churches are overviewed as a challenge to the African church to use the Old Testament in its dealings with people living with HIV and Aids.
Free